2018
DOI: 10.1093/police/pay058
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Motivations, Morale, and Retention of Special Constables: Findings from a National Survey

Abstract: Special Constables have an established history within British policing. The Special Constabulary has represented an under-researched aspect of policing, with motivations to join, morale, factors relating to length of service and reasons for leaving being poorly understood. This article draws upon data from a national survey of Special Constables undertaken across all police forces in England and Wales. The analysis illustrates differences in motivations, dependent on age, and length of service, with younger Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…When individuals require a reference or evidence of their volunteering, a letter is produced stating the dates that the person has volunteered between and the number of hours they have committed; however, the nature of the roles undertaken is not articulated, perhaps a missed opportunity to promote the knowledge and skills which can be developed as a volunteer. This supports the findings of Carpenter and Myers (2010), who identify that image and recognition of the volunteer is important and, although not specifically related to PSVs, Callender et al (2018a) who emphasise the impact of recognition and appreciation on the experience and retention of SC.…”
Section: Motivation Through Reward and Recognitionsupporting
confidence: 84%
“…When individuals require a reference or evidence of their volunteering, a letter is produced stating the dates that the person has volunteered between and the number of hours they have committed; however, the nature of the roles undertaken is not articulated, perhaps a missed opportunity to promote the knowledge and skills which can be developed as a volunteer. This supports the findings of Carpenter and Myers (2010), who identify that image and recognition of the volunteer is important and, although not specifically related to PSVs, Callender et al (2018a) who emphasise the impact of recognition and appreciation on the experience and retention of SC.…”
Section: Motivation Through Reward and Recognitionsupporting
confidence: 84%
“…The latest foreign literature authors, among others, Schafer and Herrington (2018) in “Police leadership: a comparative consideration of legislative imperatives in the United Kingdom, Australia, and the United States” (2018), Callender et al (2018) in “Understanding the motivations, morale, and retention of special constables: findings from a national survey” and Volle (2014) in “Public service motivation, role ambiguity, and job satisfaction among municipal police officers,” have written about police motivation. The publications in question present motivation strategies in different national systems and sets of motivators and factors of professional satisfaction of police officers in various countries.…”
Section: Introductionmentioning
confidence: 99%
“…Wolf et al (2015) found that the more volunteers were provided similar responsibilities to regular members, the more satisfied they were with their experiences. Morale has also been linked to retaining volunteers (Callender et al, 2020).…”
Section: Auxiliary Police Experiences and Motivations To Volunteermentioning
confidence: 99%
“…341). Therefore, explanations of motivations for volunteering as an auxiliary member are sometimes closely tied to wanting to become a regular officer at a police service (Callender et al, 2020;Millie, 2019;Pepper, 2014) and to developing personally by acquiring new skills and knowledge about policing (Ramshaw and Cosgrove, 2020;Wolf et al, 2015).…”
Section: Auxiliary Police Experiences and Motivations To Volunteermentioning
confidence: 99%